DEVELOPMENT OF A LOCAL CULTURE-BASED OUTING CLASS GUIDE AS AN EDU-RECREATIONAL PROGRAM FOR ELEMENTARY STUDENTS - Ilham Alafiannurmansyah; bambang priyono (Journal of Physical Education and Sports, 2026)
This study aimed to develop a Local Culture-Based Outing Class Guide as an edu-recreational program and an education tourism innovation for elementary school students in Jepara Regency. The background of this research is the low level of students' physical activity, limited social interaction, and the lack of structured, outing class guidelines that integrate local cultural values. this research employed a Reseach and Development (R&D) approach using the Borg and Gall model. the subjects involved elementary elementary school student, physical education teachers, outing class practitioners, and expert validators. Data were collected through interviews, questionnaires, observation, and expert validation sheets. The results showed that the developed guide integrates experiental learning principles, traditional games, local cultural values, and educational tourism concepts. Expert validation result indicated that the product was highly feasible, with an average feasibility score above 85%. student and teacher responses also showed positive perceptions regarding enjoyment, learning experiences, and cultural appreciation. The study concludes that the Local Cultur-Based Outing Class Guide is suitable to be used as an edu-recreational learning medium and has potential to support physical activity, character education, and local cultural preservation in elementary schools